MARGARITA JOVER, ALEX WALL - Ecologies of Prosperity for the living city - Monclús , Javier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2021)
Margarita Jover, Alex WallEcologies of Prosperity for the living city Virginia: AR+D Applied Research + Design Publishing. University of Virginia School of Architecture, 2019. 350 p. Language: English. Softcover. 40 $ISBN: 978-1-940743-50-9